2016
DOI: 10.1590/s0080-623420160000100019
|View full text |Cite
|
Sign up to set email alerts
|

Composition of the electrocautery smoke: integrative literature review

Abstract: Objective:To identify the composition of the smoke produced by electrocautery use during surgery. Method: Integrative review with search for primary studies conducted in the databases of the US National Library of Medicine National Institutes of Health, Cumulative Index to Nursing and Allied Health Literature, and Latin American and Caribbean Health Sciences, covering the studies published between 2004 and 2014. Results: The final sample consisted of 14 studies grouped into three categories, namely; polycyclic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 26 publications
(65 reference statements)
0
17
0
1
Order By: Relevance
“…The concordance index (IVC) among experts in the degree of accuracy of nursing diagnoses was calculated as follows: the number of experts who rated the nursing diagnoses as “High Accuracy” was divided by the total number of experts. Researchers considered an IVC equal to or greater than 0.80 as high accuracy 14 .…”
Section: Methodsmentioning
confidence: 99%
“…The concordance index (IVC) among experts in the degree of accuracy of nursing diagnoses was calculated as follows: the number of experts who rated the nursing diagnoses as “High Accuracy” was divided by the total number of experts. Researchers considered an IVC equal to or greater than 0.80 as high accuracy 14 .…”
Section: Methodsmentioning
confidence: 99%
“…The data in Table 1 were mainly from literatures [15][16][17]. All experiments were performed over 20 min on commercialised pork meat or pork liver from fresh slaughtering, including the adherent subcutaneous fatty tissue and skin.…”
Section: Data Sourcesmentioning
confidence: 99%
“…National and international studies have shown that surgical smoke contains volatile organic compounds (VOCs) (6)(7) , especially PAH (7)(8)(9) , such as benzene, benzo(a)pyrene, anthracene, naphthalene, and toluene (9) . Therefore, surgical smoke is a potential occupational hazard, in view of the amount of harmful chemicals it contains.…”
Section: Introductionmentioning
confidence: 99%